SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE DI INDONESIA - Purnamayanti, Ni Kadek Diah; Gayatri, Galih (Coping: Community of Publishing in Nursing, 2023)
Meeting the patient's basic needs related to the spiritual aspect is often not a concern. The Covid-19 pandemic is a momentum for awakening the spiritual dimension in overcoming the problem of unexpected change. Nurses in their role as service providers need to have sufficient understanding to be able to respond to the patient's spiritual needs. Meeting spiritual needs in Indonesia is quite complicated because it is often related to religion, customs, and culture. The purpose of this study was to describe the clinical application of SEFT in Indonesia. This research is a literature review using the keyword SEFT or "Spiritual Emotional Freedom Technique". The search was carried out on a trusted database in Indonesia, namely Indonesia Onesearch. The inclusion criteria are clinical studies conducted in 2017-2022. Exclusion criteria are literature review research and expert opinion. The results of the research are 9 SEFT quasi-experimental studies in Indonesia. The results of this mapping study were conducted in West Sumatra (12,5%), West Java (12,5%), Jakarta (25%), Central Java (12,5%), Yogyakarta (12,5%), East Java (25%). The research outcomes included psychosocial issues including anxiety (37,5%), aggressive behavior (12,5%), smoking habits (12,5%), stress and work motivation (12,5%). The conclusion of this study is that SEFT can be recommended as an alternative complementary therapy in Indonesia.